The Amulet of Power - Arroyo, Raymond (Will wilder, 2019)
When twelve-year-old Will Wilder uses the Amulet of Power to get on the Perilous Falls football team, he attracts dark forces that shadow townspeople, disturb graves, and lull many into a stupor.